Adopting the public on satellite channels - Fayek Rachid, Manhal; Aboud Jarallah, Nada (ALBAHITH ALALAMI, 2021)
The importance of television has emerged as an effective and influential force in the lives of societies and peoples, And not just a professional media since the fifties of the twentieth century, It was used as a platform to achieve the goals and objectives of the media and politics for governments, agencies and individuals in different countries of the world, Using many methods, methods and techniques that later became important major subjects and curricula and a scientific specialization that was founded for him to study and teach in most international universities, The media, especially television and satellite channels, play an active and significant role in managing crises and conflicts and directing them through the methods of dealing with various news, And in the process of selecting information supporting one of the parties to the crisis, or finding solutions that limit or end the crisis. The successive events, crises and turbulent conditions that Iraq has experienced since 2003 have contributed To double the importance and role of the media in general and Iraqi satellite channels in particular, Through its coverage of these events and crises, it has played a prominent, influential and directing role In its spread, expansion, exacerbation, or limitation and decline And sometimes find solutions